2017
DOI: 10.3389/fphar.2017.00141
|View full text |Cite
|
Sign up to set email alerts
|

Serelaxin Treatment Reduces Oxidative Stress and Increases Aldehyde Dehydrogenase-2 to Attenuate Nitrate Tolerance

Abstract: Background: Glyceryl trinitrate (GTN) is a commonly prescribed treatment for acute heart failure patients. However, prolonged GTN treatment induces tolerance, largely due to increased oxidative stress and reduced aldehyde dehydrogenase-2 (ALDH-2) expression. Serelaxin has several vasoprotective properties, which include reducing oxidative stress and augmenting endothelial function. We therefore tested the hypothesis in rodents that serelaxin treatment could attenuate low-dose GTN-induced tolerance.Methods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Previous studies have confirmed that mitochondrial ALDH2 has the functions of reducing oxygen free radical production, scavenging aldehydes and 4-HNE, and finally protecting mitochondrial function [24, 25]. Zhang et al [26] observed that activation of ALDH2 protects rats from hepatic ischemia/reperfusion injury by inhibiting oxidative stress and clearing the accumulation of 4-HNE.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that mitochondrial ALDH2 has the functions of reducing oxygen free radical production, scavenging aldehydes and 4-HNE, and finally protecting mitochondrial function [24, 25]. Zhang et al [26] observed that activation of ALDH2 protects rats from hepatic ischemia/reperfusion injury by inhibiting oxidative stress and clearing the accumulation of 4-HNE.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that relaxin may regulate eNOS function at a post‐translational level to increase NO bioavailability. We have previously shown that relaxin enhances NOS activity via reduction of vascular oxidative stress (Leo et al, ), activation of eNOS phosphorylation at Ser 1177 (Leo et al, ; Leo, Jelinic, Parkington, et al, ; McGuane et al, ), and up‐regulation of eNOS dimerisation (Jelinic et al, ). Furthermore, the ability of relaxin to increase NO bioavailability and prevent endothelial dysfunction is observed in a number of disease conditions, including TNF‐α incubation (Dschietzig et al, ), cigarette smoke (Pini et al, ), arteriosclerosis (Tiyerili et al, ), and diabetes (Ng et al, ; Ng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The aortae were mounted on a wire myograph (model 610M; Danish Myo Technology, Aarhus, Denmark) as described previously [41,[58][59][60] with the following modifications. Briefly, the aorta was allowed to stabilize at zero tension for 15 min, followed by a 30 min equilibrium at 5mN.…”
Section: Assessment Of Vascular Reactivitymentioning
confidence: 99%